2016
DOI: 10.1093/jac/dkw293
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin B in combination with doripenem against heteroresistant Acinetobacter baumannii : pharmacodynamics of new dosing strategies

Abstract: Objectives: Polymyxin B is being increasingly utilized as a last resort against resistant Gram-negative bacteria. We examined the pharmacodynamics of novel dosing strategies for polymyxin B combinations to maximize efficacy and minimize the emergence of resistance and drug exposure against Acinetobacter baumannii. Methods:The pharmacodynamics of polymyxin B together with doripenem were evaluated in time -kill experiments over 48 h against 10 8 cfu/mL of two polymyxin-heteroresistant A. baumannii isolates (ATCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
(30 reference statements)
1
27
0
Order By: Relevance
“…The model was able to describe bacterial dynamics based on these mechanisms. The estimated bacterial growth rate constant ( kg: 0.327 h −1 ; representing net replication) was comparable to previous studies modeling A. baumannii . As neutrophils were the only measured immune cells, transit compartments were used to represent neutrophil signaling.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The model was able to describe bacterial dynamics based on these mechanisms. The estimated bacterial growth rate constant ( kg: 0.327 h −1 ; representing net replication) was comparable to previous studies modeling A. baumannii . As neutrophils were the only measured immune cells, transit compartments were used to represent neutrophil signaling.…”
Section: Discussionsupporting
confidence: 53%
“…The estimated bacterial growth rate constant (k g : 0.327 h 21 ; representing net replication) was comparable to previous studies modeling A. baumannii. 29,30 As neutrophils were the only measured immune cells, transit compartments were used to represent neutrophil signaling. Transit compartments serve as placeholders for these natural antibacterial processes to be quantified in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Schemes of high-dose PMB to overcome the emergence of resistance to this antibiotic during exposure have been evaluated in in vitro infection models, with promising results (14)(15)(16)(17). Moreover, few observational studies have suggested that increased doses might be associated with improved clinical outcomes (8)(9)(10)18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, resistance to both polymyxins has increasingly been reported, and in vitro studies have shown that the emergence of resistance is relatively common even by isolates exposed to polymyxin concentrations similar to those expected in vivo after the administration of an adequate dose of polymyxins (11)(12)(13). To counteract this occurrence, in vitro exposures to very high concentrations of PMB through the use of distinct strategies, such as administration of a loading dose or the use of high doses in combination schemes, have been evaluated, with promising results (14)(15)(16)(17). However, the toxicity of such regimens, in particular, the toxicity related to the infusion of high doses, is largely unknown.…”
mentioning
confidence: 99%
“…1 Strategies involving higher doses, longer dosing intervals, loading doses, extended infusions, and pharmacokinetic/pharmacodynamic (PK/PD) principles have been proposed to optimize efficacy and prevent the development of resistance. [178][179][180] However, colistin has relatively poor PK/PD properties, and it may be difficult to achieve high enough serum concentrations quickly. 155 CMS (a prodrug) has to be converted to the active form (colistin) in the plasma, and concentrations may be suboptimal for 2 to 3 days until a steady state is achieved; thus, a loading dose is recommended.…”
Section: Polymyxins (Colistin)mentioning
confidence: 99%